What anatomy is clinically useful and when should we be teaching it?. Issue 5 (5th February 2016) - Leveritt, Simon; McKnight, Gerard; Edwards, Kimberley; Pratten, Margaret; Merrick, Deborah
Abstract : Anatomy teaching, once thought of as being the cornerstone of medical education, has undergone much change in the recent years. There is now growing concern for falling standards in medical graduates' anatomical knowledge, coupled with a reduction in teaching time and appropriately qualified teaching staff. With limited contact hours available to teach this important discipline, it is essential to consider what anatomy is taught within the medical curriculum to ensure it is fit for clinical practice. The views of medical students, junior doctors, and consultants were obtained from the University of Nottingham and the Trent Deanery in Nottingham, United Kingdom, to establish what core anatomical knowledge they feel medical students should study and assimilate during preclinical training. All participants felt strongly that medical students should be adept at interpreting modern diagnostic images before entering their clinical placement or specialty. Respondents proposed more teaching emphasis should be placed on specific anatomical areas (including lymphatic drainage and dermatome innervation) and illustrated other areas where less detailed teaching was appropriate. Recommendations from our study highlight a need for greater clinical emphasis in anatomy teaching during preclinical years. To successfully achieve this, it is essential that clinicians become integrally involved in the design and delivery of future medical undergraduate anatomy courses. Anat Sci Educ 9: 468–475. © 2016 American Association of Anatomists.